1989
DOI: 10.1161/01.cir.79.2.287
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of endothelial dysfunction in angiographically normal coronary arteries of patients with coronary artery disease.

Abstract: Acetylcholine causes endothelium-dependent dilation of normal arteries in most animal species. The effect of acetylcholine on normal human coronary arteries is controversial. Pathologic studies and epicardial echocardiography have shown that diffuse atherosclerosis is often present despite angiographic evidence of discrete coronary artery disease (CAD). Therefore, we postulated that acetylcholine would cause vasoconstriction of coronary arteries that are angiographically normal in patients with CAD. Coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
6

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(86 citation statements)
references
References 29 publications
1
79
0
6
Order By: Relevance
“…Endothelium-derived NO, therefore, is protective for the vasculature and decreased NO bioavailability is often associated with increased risk of cardiovascular disease [62]. As mentioned, endothelial dysfunction is one of the earliest manifestations of atherosclerosis [63].…”
Section: Statins and Vascular Dysfunctionmentioning
confidence: 99%
“…Endothelium-derived NO, therefore, is protective for the vasculature and decreased NO bioavailability is often associated with increased risk of cardiovascular disease [62]. As mentioned, endothelial dysfunction is one of the earliest manifestations of atherosclerosis [63].…”
Section: Statins and Vascular Dysfunctionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Clinical studies have shown that intracoronary acetylcholine infusion constricts atherosclerotic coronary arteries.9-11 Smooth segments may also constrict in patients with coronary artery disease evident in other vessels, possibly reflecting early atherosclerosis.11 In patients with angiographically "normal" coronary arteries, the vasomotor response to intracoronary acetylcholine is heterogeneous: both dilation and constriction have been reported. [10][11][12][13] This study examines the hypothesis that coronary risk factors disturb endothelial function and may thereby influence the response to intracoronary acetylcholine in patients with angiographically smooth coronary arteries. Methods …”
mentioning
confidence: 99%
“…When acetylcholine was infused intravenously, normal controls showed a vasodilatory response, but responses were reduced or vasoconstrictive in patients with hypertension, 13 diabetes, 15 hypercholesterolemia, 14 congestive heart failure 28 or atherosclerosis. 5,21,[23][24][25] Similarly, increases in flow subject the endothelium to increased shear stress, which stimulates the NO-cGMP pathway, so that FMD is also dependent on endothelial cells. Abnormal FMD has been shown in patients with cardiac risk factors and in atherosclerosis.…”
Section: No-dependent Penile Erectionmentioning
confidence: 99%
“…4,[6][7][8][9][10][11] Cardiac risk factors are prevalent in patients with ED 12 and correlate with endothelial dysfunction, including hypertension, 13 hypercholesterolemia, 3,14,15 diabetes, 6,15 smoking 3, [16][17][18] and age, 18 as well as with atherosclerosis. 3,[19][20][21][22][23][24][25] This study reviews normal endothelial function, as well as endothelial dysfunction in general and related specifically to ED. A variety of methods to measure endothelial function and therapies that improve endothelial function are reviewed.…”
Section: Introductionmentioning
confidence: 99%